2020
DOI: 10.4314/ijs.v21i3.19
|View full text |Cite
|
Sign up to set email alerts
|

Food grade carboxymethyl cellulose preparation from African star apple seed (<i>Chrysophyllum albidum</i>) shells: optimization and characterization

Abstract: α-cellulose isolated from African star apple seed shell (ASASS) was used as the raw material for the production of food-grade carboxymethyl cellulose (CMC). Preparation of CMC from ASASS cellulose was carried out by an etherification process, using sodium hydroxide and monochloroacetic acid (MCA) at various temperature. The cellulose and CMC were characterized by FTIR, XRD and SEM techniques. Degree of substitution (DS) was determined using potentiometric titration. Solubility increased with DS of CMC increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…In particular, the value of DS can be fine-tuned by the concentration of reagents like isobutanol, ethanol, NaOH, and etherification agent (MCA). For example, depending on the varying concentration of NaOH, V. Pushpamalar (2006) [ 5 ]; P. Rachtanapun et al (2012) [ 9 ]; A. H. Saputra et al (2014) [ 140 ]; M. S. Yeasmin et al (2015) [ 119 ]; and Ibikunle et al (2020) [ 141 ] reported a range of DS of 0.51–0.82 (for sago waste) [ 5 ]; 0.56–0.87 (for durian rind) [ 9 ]; 0.14–1.76 (for water hyacinth) [ 140 ]; 0.1–2.41 (for corn husk) [ 119 ]; and 0.15–0.93 (for African star apple seed shell) [ 141 ], respectively. A higher DS value was determined mostly against 30% NaOH [ 116 , 119 , 141 ] and negligible at 25% and 10% NaOH [ 5 , 140 ].…”
Section: Characteristics Of Cmcmentioning
confidence: 99%
“…In particular, the value of DS can be fine-tuned by the concentration of reagents like isobutanol, ethanol, NaOH, and etherification agent (MCA). For example, depending on the varying concentration of NaOH, V. Pushpamalar (2006) [ 5 ]; P. Rachtanapun et al (2012) [ 9 ]; A. H. Saputra et al (2014) [ 140 ]; M. S. Yeasmin et al (2015) [ 119 ]; and Ibikunle et al (2020) [ 141 ] reported a range of DS of 0.51–0.82 (for sago waste) [ 5 ]; 0.56–0.87 (for durian rind) [ 9 ]; 0.14–1.76 (for water hyacinth) [ 140 ]; 0.1–2.41 (for corn husk) [ 119 ]; and 0.15–0.93 (for African star apple seed shell) [ 141 ], respectively. A higher DS value was determined mostly against 30% NaOH [ 116 , 119 , 141 ] and negligible at 25% and 10% NaOH [ 5 , 140 ].…”
Section: Characteristics Of Cmcmentioning
confidence: 99%
“…Cellulose neither melts nor dissolves readily in hot or cold water solvents due to its strong inter- and intramolecular hydrogen bonds to nearby oxygen [ 44 ]. It has other undesirable properties, such as moisture sensitivity and low resistance to microbial attacks [ 44 , 45 , 46 ]. Therefore, this polymer should ideally be converted into more amenable derivatives.…”
Section: Cellulose and Carboxymethyl Cellulose And Their Propertiesmentioning
confidence: 99%
“…About 0.2 mg of sample and 2 mg of potassium bromide were mixed and ground finely before the mixture was compressed to pellet. The infrared spectra of these samples were measured in the transmission of a wavelength -1n umber range between 4000 and 400 cm [27] .…”
Section: Fourier Transformed Infrared Spectroscopy (Ftir)mentioning
confidence: 99%